Segodnia v mire . Segodnia v mire . The World Today . Сегодня в мире - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Nuclear tests near Los Angeles; illegal toxic waste exports to Venezuela; Aboriginal deaths in Australian prisons. Contributors: Biriukov, Dmitrii (Anchor) Series description: An information program of the Central Television of the USSR (CT USSR). The hosts were Igor Fesunenko, Valentin Zorin, Farid Seiful-Muliukov, and others. The program was first broadcasted on December 1, 1978 and was broadcasted until 1988. Проведение испытательного взрыва на полигоне в Лос-Анджелесе; нелегальный ввоз ядовитых отходов в Венесуэлу; о случаях гибели аборигенов в тюрьмах Австралии. Создатели: Бирюков, Дмитрий (Ведущий/Ведущая) Описание серии: Информационная телепередача Центрального телевидения СССР. Ведущие — Игорь Фесуненко, Валентин Зорин, Фарид Сейфуль-Мулюков и другие. Первый выпуск передачи вышел в эфир 1 декабря 1978 года. Выходила до 1988 года